The Influence of Product Quality and Price on Purchasing Decisions at Kaku Food, Makassar City - Suci Ramadani; Aulia; Asdar (Pustaka Digital Indonesia, 2024)
The purpose of this research is a quantitative study aimed at understanding the influence of product quality and price on purchasing decisions at Kaku Food in Makassar City. The sample was taken from students of the Management Department, Class of 2020, at the Muhammadiyah University of Makassar. The type of data used in this research is quantitative data obtained from distributed questionnaires, which are related to the research problem. In this study, the data sources include both primary and secondary data. The research instrument employed in this study uses the Likert scale method. The data was analyzed using the Statistical Package for the Social Sciences (SPSS) version 25 to examine the influence of product quality and price on purchasing decisions at Kaku Food in Makassar City, as discussed in the previous chapters. This is evidenced by the value of the product quality variable (X1), where the calculated t-value is 4.085, which is greater than the table t-value of 1.996. Additionally, for the price variable (X2), the calculated t-value is 7.462, which is also greater than the table t-value of 1.996. From these results, the researcher concludes that both product quality and price have a positive and significant effect on purchasing decisions. These findings suggest that product quality needs to be further enhanced, and the prices offered should align with the quality received by consumers. This alignment ensures customer satisfaction and loyalty, which are crucial for the continued success of Kaku Food in a competitive market. Furthermore, understanding these dynamics can help Kaku Food strategize better in terms of marketing and product development, ensuring that they meet consumer expectations effectively. This research underlines the importance of both product quality and pricing strategies in shaping consumer behavior and decision-making in the food industry.